Bentuk Bencana Perspektif Hadis - muhtadin ahmadsyah; Emri Agus (Institut Agama Islam Sumatera Barat, 2024)
Natural disasters and unforeseen events have been phenomena that have plagued humanity throughout history. In Islam, the hadiths of Prophet Muhammad ﷺ provide guidance and knowledge about various types of disasters that can occur. This article aims to analyze the different types of disasters mentioned in thematic hadiths. The research method employed in this article is literature analysis, focusing on hadiths discussing natural disasters, diseases, warfare, and others. This study also involves a critical review of hadith narrations and interpretations by scholars to understand the meanings and implications of disasters in the context of thematic hadiths. The analysis results indicate that thematic hadiths mention various types of disasters, including earthquakes, floods, droughts, diseases, wars, and others. These hadiths provide knowledge about the causes of disasters, signs of their occurrence, and how Muslims should respond to them. The article also discusses the relevance of hadiths about disasters in modern contexts. This literature analysis is expected to provide a better understanding of disasters and serve as a valuable source of information for the Muslim community in facing disasters,